Clusterin as a therapeutic target. (1st February 2017) - Wilson, Mark R.; Zoubeidi, Amina
ABSTRACT: Introduction : Clusterin (CLU) is a stress-activated, ATP-independent molecular chaperone, normally secreted from cells, that is up-regulated in Alzheimer disease and in many cancers. It plays important roles in protein homeostasis/proteostasis, inhibition of cell death pathways, and modulation of pro-survival signalling and transcriptional networks. Changes in the CLU gene locus are highly associated with Alzheimer disease, and many therapy-resistant cancers over-express CLU. The extensive post-translational processing and heterogeneous oligomerization of CLU have so far prevented any definitive structure determination. This in turn has meant that targeting CLU with small molecule inhibitors is challenging. Therefore, inhibiting CLU at the gene-expression level using siRNA or antisense is a valid approach to inhibit its function. Areas covered : This article reviews recent advances regarding the role of CLU in proteostasis, cellular trafficking, human diseases, and signalling pathways involved in oncogenesis. It addresses the rationale for CLU as a therapeutic target in cancer, and the current status of pre-clinical and clinical studies using CLU antisense inhibitor OGX011. Expert opinion : Discusses challenges facing the therapeutic targeting of CLU including rapid changes in the treatment landscape for prostate cancer with multiple new FDA approved drugs, selection of windows of intervention, and potential side effects when silencing CLU expression.